2009
DOI: 10.2353/ajpath.2009.080868
|View full text |Cite
|
Sign up to set email alerts
|

Novel Biomarkers for Prostate Cancer Including Noncoding Transcripts

Abstract: Levels of 27 transcripts were investigated as potential novel markers for prostate cancer, including genes encoding plasma membrane proteins (ADAM2, ELOVL5, MARCKSL1, RAMP1, TMEM30A, and TMEM66); secreted proteins (SPON2, TMEM30A, TMEM66, and truncated TMEFF2 (called POP4)); intracellular proteins (CAMK2N1, DHCR24, GLO1, NGFRAP1, PGK1, PSMA7, SBDS, and YWHAQ); and noncoding transcripts (POP1 (100 kb) from mRNA AK000023), POP2 (4 kb from mRNA AL832227), POP3 (50 kb from EST CFI40309), POP5 (intron of NCAM2, acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
93
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(97 citation statements)
references
References 62 publications
4
93
0
Order By: Relevance
“…Using biotinylation analysis we detected SARAF expressed in the PM, which is consistent with the suggested location of the product of TMEM66 in prostate cancer cells (18). Furthermore, we have found that SARAF in the PM is able to associate with Orai1 and this interaction is enhanced by stimulation with AA.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…Using biotinylation analysis we detected SARAF expressed in the PM, which is consistent with the suggested location of the product of TMEM66 in prostate cancer cells (18). Furthermore, we have found that SARAF in the PM is able to associate with Orai1 and this interaction is enhanced by stimulation with AA.…”
Section: Discussionsupporting
confidence: 68%
“…As depicted in Fig. 2B (17); however, the product of TMEM66, the former name of the gene encoding SARAF, has been suggested to be located in the PM (18). Since ARC channels consist of a heteropentameric complex of three Orai1 and two Orai3 subunits with the participation of PM-resident STIM1 (4 -5) we investigated whether there is a pool of SARAF constitutively expressed in the PM and whether SARAF interacts with ARC channels.…”
Section: Saraf Modulates Camentioning
confidence: 99%
“…In other studies, the TMEM66 gene was expressed among different novel androgen-responsive genes in prostate cancer. Those genes were indicated to play a role in the molecular mechanisms of androgen-dependency of the prostate and were also considered as targets for therapy or biomarkers of prostate cancer (29,30).…”
Section: Discussionmentioning
confidence: 99%
“…The early studies had showed that TNFAIP8 is an oncogenic factor that may play a role in tumor progression, and exogenous expression of TNFAIP8 enhances cell survival. proliferation and inhibition of activities of the apoptotic enzymes caspase 8 and caspase 3 (You et al, 2001;Romanuik et al, 2009). Human breast cancer cells transfected with TNFAIP8 increased proliferation, cell migration, and tumor growth rate (Kumar et al, 2004).…”
Section: Introductionmentioning
confidence: 99%